2021
DOI: 10.1186/s12888-021-03070-z
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for occupational therapy interventions for adults with ADHD: a consensus statement from the UK adult ADHD network

Abstract: Background ADHD is neurodevelopmental disorder which persists into adulthood. Presently, therapeutic approaches are mainly pharmacological and psychological whilst the role, scope and approaches of occupational therapists have not been adequately described. Results In this consensus statement we propose that by assessing specific aspects of a person’s occupation, occupational therapists can deploy their unique skills in providing specialist interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In conclusion, this study has shown that ADHD symptoms are associated with higher odds for stress and that in turn, stress is an important factor in the association between ADHD symptoms and suicidal ideation. As there is some indication that individuals with ADHD/ADHD symptoms may use maladaptive coping strategies in response to stressful situations ( 63 ), some of which may be linked to increased life impairments ( 64 ), then the results of this study underscore the importance of identifying sources of stress in this population and of both developing and fostering the use of stress management techniques ( 65 ) and adaptive stress coping strategies ( 64 ).…”
Section: Discussionmentioning
confidence: 93%
“…In conclusion, this study has shown that ADHD symptoms are associated with higher odds for stress and that in turn, stress is an important factor in the association between ADHD symptoms and suicidal ideation. As there is some indication that individuals with ADHD/ADHD symptoms may use maladaptive coping strategies in response to stressful situations ( 63 ), some of which may be linked to increased life impairments ( 64 ), then the results of this study underscore the importance of identifying sources of stress in this population and of both developing and fostering the use of stress management techniques ( 65 ) and adaptive stress coping strategies ( 64 ).…”
Section: Discussionmentioning
confidence: 93%
“…In terms of clinical implications, our results suggest that interventions aiming to reduce individuals’ stress responses may be beneficial in reducing the co-occurrence of ADHD symptoms and internalising problems. Stress management techniques are already recommended as part of occupational therapy interventions for adults with ADHD in the United Kingdom (Adamou et al, 2021 ). Stress management interventions such as mindfulness-based stress reduction training or cognitive behavioural therapy have been found to effectively reduce stress and improve wellbeing in individuals suffering from depression or anxiety (Carpenter et al, 2018 ; Chi et al, 2018 ; Otte, 2011 ), however, to date, little is known about the efficacy of such techniques for preventing the development of internalising problems as secondary to ADHD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study indicate deficiencies in both the provision and the acceptability of non-pharmacological treatment for adult ADHD, among working adults. This includes occupational therapy, as very few participants in the current study had ever been in contact with an occupational therapist, despite consensus among ADHD experts regarding the importance of occupational therapists in ADHD interventions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%